Analisis Elektrofasies Berdasarkan Data Well Logging pada Seam Batubara A1–D di Pit N, Tanjung Enim, Sumatera Selatan - Muhammmad Rafi Al Hawari Rafi; Harnani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The equitable distribution of educational facilities is a crucial aspect of supporting sustainable regional development, particularly at the senior high school level as part of the secondary education system. Inequality in school distribution may affect accessibility and equal educational opportunities across regions. This study aims to analyze the spatial distribution patterns and service coverage of senior high school facilities in Kabupaten Magetan. The research employs a quantitative approach using Geographic Information System (GIS)-based spatial analysis. Analytical techniques include mapping school distribution, applying the Average Nearest Neighbor (ANN) analysis to identify distribution patterns, and conducting buffer analysis to evaluate service accessibility to residential areas. The results indicate that educational facilities tend to form clustered patterns in areas with higher accessibility levels. Service coverage analysis also reveals disparities in accessibility among regions, where central areas demonstrate better service coverage compared to peripheral zones. These findings suggest that the equitable distribution of educational facilities still requires optimization in spatial planning to enhance educational access equity and support sustainable regional development.